PENGUATAN PENDIDIKAN AQIDAH ISLAM PADA ANAK SEBELUM USIA AQIL BALIGH - AS. FM, D. Zahra; Ritonga, Apri Wardana; Atansyah, Awis; Auliya, Anisa (IAIN Madura, 2023)
This study aims to determine the urgency of Islamic aqeedah education for children before reaching puberty, the implementation process, and its strengthening for children in the family environment. This research uses a qualitative descriptive approach with the method of literature study. Data was collected from various primary and secondary sources in the form of Al-Qur'an, books, and scientific articles. The data is then classified, analyzed, and interpreted in a descriptive narrative. The results of this study reveal that: first, the urgency of Islamic belief is the main catalyst that must be taught to children before the age of puberty; second, the implementation of Islamic aqeedah can be in the form of stimulation by parents in the family environment; third, strengthening Islamic faith in children can be done by applying exemplary methods, ta'wîdiyyah, mau'izhah, qashash, amtsâl, tsawâb, and 'iqâb. The research findings illustrate that Islamic faith education is the responsibility of all parties, both parents, the community as well as teachers in educational institutions. Through this research, the researcher recommends further research to describe the efforts of educational institutions in strengthening Islamic faith education for students in Indonesia using more comprehensive samples, approaches, and methods.